ANALISIS KUALITAS PELAYANAN FASILITAS TERMINAL KAMPUNG RAMBUTAN BERDASARKAN TINGKAT KEPUASAN PENGGUNA - Rizka Kurniawati; Nuryani Tinumbia (Jurnal Infrastruktur, 2019)
The existence of a bus station in the transportation network is very important, because it is a place of modal transfer. Kampung Rambutan bus station is a Type-A bus station that serves transportation of intercity interprovincial (AKAP) and intercity within DKI Jakarta (AKDP). Thus the performance of the terminal is very important in order to support the smooth running, safety and comfort of passengers in modal transfer. This study aims to determine the service quality of Kampung Rambutan bus station to user satisfaction, determine the existing performance based on Minimum Service Standards (SPM), and provide recommendations for improving the facilities of Kampung Rambutan bus station. The survey was conducted by distributing questionnaires to the users (passengers) and inventorying the existing condition of the bus station. Analysis using Importance-Performance Analysis (IPA) and descriptive statistics. The analysis shows that there are several indicators become the main priority for improvement according to the users, namely facilities for disability users, delivery of bus departure and arrival information, safety and comfort.